O hipertexto em sala de aula: uma proposta metodológica para o ensino de Língua Portuguesa - Caldas, Alba Helena Fernandes (2014)
This research aims to introduce a methodological proposal for the teaching of hypertext reading in Portuguese language classes based on text and hypertexts studies in the sociocognitive and interactionist perspectives, as they are developed in the context of Text Linguistics. To answer the core issue of the research how to elaborate a methodological proposal for the teaching of hypertext reading in basic education it is necessary to study: i) how the curriculum documents of Portuguese language deal with reading of digital texts; ii) how the textbooks of the National Textbook Program (PNLD) of Portuguese language in basic education deal with reading of digital texts; iii) how the teachers of Portuguese language in basic education deal with reading of digital texts in the classroom. Hence, from the methodological point of view, were adopted as procedure: 1) the study of the official documents of Portuguese language, the National Curricular Parameters PCN (BRASIL, 1998) and the Common Basic Contents CBC (MINAS GERAIS, 2005), which lead the teachers educational practice in basic education at public schools; 2) the verification of how the textbooks deal with reading of digital texts; 3) analysis of the data collected from a questionnaire about the facilities and difficulties that the teachers face in basic education during the use of digital texts in the classroom; 4) theoretical studies about texts and hypertexts in the sociocognitive and interactionist perspectives; 5) introduce a methodological proposal for the teaching of hypertext reading. The proposal brings two interrelated steps: the first one focuses components and characteristics of the hypertext which interfere in the readout mode; the second step focuses the activation of links and construction of meanings based in different foreknowledges of the reader and the objectives while reading. Overall, the proposal turns to the improvement of reading and construction of meanings activities in times of digital culture